Rethinking Human Rights from Decolonial Criticism: situating possible discourses and realistic paths through social struggles - Marques Gervásio, Ana Laura (2023)
The text proposes to discuss within the scope of decolonial theories, to promote cultural-geographic-politically situated critiques of human rights. It is necessary to find ways for the perception of practical obstacles in the application of these rights in the global South, based on a dialogue of decolonial theories with the proposals of the Spanish professor Joaquín Herrera Flores so that it is possible to locate the discourses and seek realistic paths on human rights. It was sought to contribute to productions of situated criticism, finding possibilities that can provide the construction of new cultures of human rights, guided by notions of human dignities found in the midst of social struggles. It uses an interdisciplinary perspective of theoretical research, with a qualitative nature, enabling a historical, anthropological and epistemological understanding that, from a hypothetical-deductive approach, is based on decoloniality as a plural method.